Synthesis and Application of Starch-Modified Chitosan-Silver Nanoparticle Composite as Green Corrosion Inhibitor for Mild Steel in Acidic Media - Fidudusola, Anthonia Fidamilare; Igbafe, Sylvia; Igbafe, Anselm Iuebego (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
The corrosion of mild steel in acidic environments presents a significant challenge across various industries, including oil and gas, chemical processing, and manufacturing. Traditional corrosion inhibitors, while effective, often contain toxic and environmentally harmful chemicals, prompting the need for sustainable alternatives. In this study, a novel green corrosion inhibitor composed of cassava starch-modified chitosan and silver nanoparticles (AgNPs) was synthesized, characterized and application for protecting mild steel in dilute hydrochloric acid medium. The study utilized starchy extracts from waste cassava peel with chitosan synthesized from snail shells combined with green synthesis of AgNPs using phytochemicals of starch extracts as a reducing and stabilizing agent to formulate a biopolymer composite inhibitor. The starch, chitosan, and AgNPs formulation blend was varied in ratios, and inhibition effectiveness evaluated through gravimetric analysis, electrochemical measurements, and surface characterization techniques such as Fourier transform infrared spectroscopy, x-ray diffraction, and scanning electron microscopy. Findings, demonstrated that the starch-chitosan-AgNPs composite exhibited superior corrosion inhibition efficiency, reaching up to 97% at optimal starch concentrations. It also revealed that higher starch concentrations improved the inhibitor’s performance due to increased surface coverage and adhesion. The inhibitor functioned by forming a protective film on the mild steel surface. The incorporation of AgNPs enhanced the inhibitor’s stability and barrier properties, while the biopolymers provided biodegradability and non-toxicity. This work highlights the potential of biopolymer-based green inhibitors as sustainable alternatives to conventional corrosion inhibitors.